Acute mesenterial ischaemia: a contemporary view - V. I. Podoluzhnyi; A. B. Startsev; I. A. Radionov (Фундаментальная и клиническая медицина, 2023)
During the COVID-19 pandemic, the incidence of acute mesenteric ischemia (AMI) increased to 10.9 per 100 000 population. Here we discuss causes, symptoms, current diagnosis and treatment of AMI.Frequently, such patients suffer from stenosis or occlusion of superior mesenteric artery accompanied by coronary artery disease, chronic heart failure, or chronic brain ischaemia. The main clinical symptom is constant abdominal pain which is sharp in case of mesenteric artery thrombosis or dull if thrombosis is restricted to the branch of superior or inferior mesenteric veins. Conventionally, the diagnosis of AMI is verified by multislice computed tomography angiography and contrast-enhanced multislice computed tomography. Timely diagnosis with emergency surgery reduces mortality from 90% to 30-50%. The best treatment outcomes are observed after early revascularizations and minimally invasive endovascular interventions.